Unstable simple elbow dislocations: medium-term results after non-surgical and surgical treatment - Schnetzke, Marc; Aytaç, Sâra; Keil, Holger; Deuß, Moritz; Studier-Fischer, Stefan; Grützner, Paul Alfred; Gühring, Thorsten (Knee surgery, sports traumatology, arthroscopy, 2017)
Purpose: Determination of the appropriate treatment of unstable simple elbow dislocations is difficult and a topic of ongoing discussion. The aim of this study was to analyse the outcome and complications after surgery and conservative treatment, with special focus on post-traumatic joint laxity. Methods: In this retrospective study, 118 consecutive patients with simple elbow dislocations underwent stability testing by fluoroscopy after joint reduction and were assigned to groups 1 (slight), 2 (moderate) or 3 (gross) depending on post-traumatic joint laxity. All patients of group 1 underwent conservative treatment, and of group 3 primary ligament repair. In patients with moderate elbow laxity, the treatment was decided individually. All patients underwent a similar functional rehabilitation programme during treatment. Clinical outcome was determined after an average of 3.4 ± 1.5 years using the Mayo Elbow Performance Score (MEPS), and treatment-associated complications and revisions were recorded. Results: Forty-nine patients (41.5 %) were assigned to group 1, 41 patients (34.7 %) to group 2 and 28 patients (23.7 %) to group 3. In group 2, 22 patients underwent ligament repair, while 19 patients were treated conservatively. On average, an excellent MEPS was achieved in group 1 after conservative treatment (MEPS 95.8 ± 9.0), similar to results after ligament repair of grossly unstable elbows in group 3 (91.6 ± 11.7). Interestingly, in group 2 conservative treatment was associated with a slightly lower MEPS (90.0 vs. 95.7), and significantly fewer patients achieved an excellent MEPS (81.8 vs. 52.6 %, p = 0.045). Similarly, conservative treatment in group 2 was associated with a fivefold to sixfold risk of complications (p = 0.032) and revision surgery (p = 0.023). Conclusions: This study supports the notion that patients with slight elbow laxity can be treated non-operatively, while primary surgical treatment should be performed in patients with moderate and gross laxity to avoid post-traumatic sequelae and decrease revision rates. Level of evidence: Retrospective: Cohort Study, Level III.